Single Center Experience with a 4-Week 177Lu-PSMA-617 Treatment Interval in Patients with Metastatic Castration-Resistant Prostate Cancer - Kemppainen Jukka; Kangasmäki Aki; Malaspina Simona; Pape Bernd; Jalomäki Jarno; Kairemo Kalevi; Kononen Juha; Joensuu Timo (Switzerland, 2025)
Background: 177Lu-PSMA-617 is a promising theragnostic treatment for metastatic castration-resistant prostate cancer (mCRPC). However, both the optimal treatment dose and interval in mCRPC and the rate of identification of responders from non-responders among possible treatment candidates are unknown.
Methods: 62 men with mCRPC who were treated with 177Lu-PSMA-617 during 1/2017-2/2019 were included in the study. Treatment responses, overall survival (OS) and progression free survival (PFS) were determined. The median follow-up time was 1.4 years (IQR 0.5-2.2). Tumor volume of metastases (MTV), SUVmax and tumor lesion activity (TLA) were quantitated from pre-treatment PSMA PET/CT images together with pre-treatment PSA.
Results: An average of three treatment cycles (2-5) were given within a four-week interval. PFS was 4.9 months (2.4-9.6) and OS was 17.2 months (6-26.4). There were no major adverse events reported. A significant PSA response of >50% was found in 58.7% of patients, which was significantly associated with longer OS, p < 0.004. PSA response was not associated with staging PSMA-derived parameters.
Conclusions: 177Lu-PSMA-617 treatment in four-week intervals was safe and effective. Almost 60% of patients had a significant PSA response, which was associated with better OS. Pre-treatment PSA kinetics or staging PSMA PET/CT-derived parameters were not helpful in identifying treatment responders from non-responders; better biomarkers are needed to aid in patient selection.